Effects of Counselling on Quality of Life among Cancer Patients in Malaysia: A Randomized Controlled Trial - Ummavathy PERIASAMY; Sherina MOHD-SIDIK; Mehrnoosh AKHTARI- ZAVARE; Lekhraj RAMPAL; Siti Irma Fadhilah ISMAIL; Rozi MAHMUD (Tehran University of Medical Sciences, 2020)
Background: We aimed to assess whether "Managing Patients on Chemotherapy" book is effective to improve quality of life (QOL) of cancer patient via counselling by pharmacist. Methods: A randomized control trial study was run among 2120 cancer patients in public hospitals in Peninsular Malaysia, from Apr 2016-Jan 2018. The treatment group received counselling regarding chemotherapy by using developed module. The data were collected at three time-points: baseline, 1st, 2nd and 3rd follow-ups after counseling by Validated Malay version of the WHOQOL-BREF of questionnaire. Data analyses were done using χ2 and two-way repeated measure ANOVA. Results: The treatment group improved significantly as compared to control group in physical health, psychological health, social relationship, environment and overall QOL (P<0.00). Conclusion: The "Managing Patients on Chemotherapy" book along with repetitive counselling by pharmacists is a useful intervention for improving QOL of cancer patients undergoing treatment.